STUDI PERILAKU MONYET EKOR PANJANG (Macaca fascicularis) DI TAMAN WISATA ALAM (TWA) SURANADI LOMBOK BARAT - Susi Ratnasari; Muhsinul Ihsan; Suhirman Suhirman (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2019)
This study aims to determine the behavior of long-tailed monkeys (Macaca fascicularis) in Taman Wisata Alam (TWA) Suranadi, West Lombok. This type of research is descriptive exploratory with a qualitative approach. Observation of the behavior of long-tailed monkeys was carried out in three groups, each of which was located in the west, north and east of Suranadi TWA Dam. The method of observing the behavior of long-tailed monkeys used is Scan Sampling. Each group of long-tailed monkeys was observed three times, each for 150 minutes at 5 minute intervals. The results of this study can be seen that the behavior of long-tailed monkeys in the west from highest to low yields is moving (39.26%), eating (17.66%), inactive (13.96%), grooming (11.55%) voiced (9.8%), playing (4.04%), agonistic (2.03%), sleeping (1.6%), and mating (0.1%). The behavior of long-tailed monkeys in the east from highest to low yields is moving (37.28%), noiseless (15.2%), feeding (14.53%), inactive (12.3%), grooming (11.16) %), agonistic (4.6%), play (3.63%), sleep (1.17%), and mate (0.13%). Behavior of long tailed monkeys in the north from high to low is moving (38.03%), feeding (28.64%), inactive (13.2%), noiseless (10.14%), grooming (6.42% ), agonistic (1.9%), play (1.17%), and sleep (0.5%). There are 9 types of observation points at the west and east and 8 types of behavior at the north observation point. The conclusion of this study is that the average percentage of long-tailed Monkey behavior from high to low is moving, eating, inactive, voicing, grooming, playing, agonistic, sleeping and mating.